Production of compost from organic materials and agro waste - Wan Razali, Wan Aizuddin; Samsu Baharuddin, Azhari; Muhamad, Zambahari; Sulaiman, Alawi; Dzulkornain, Chairil Anuar; Omar, Farah Nadia; Mokhtar, Mohd Noriznan; Md. Shah, Umi Kalsom (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Knowledge related to composting of organic materials and agro waste will be transferred to Bagan Datoh, Perak community through collaboration between Universiti Putra Malaysia (UPM), Universiti Teknologi MARA (UiTM) and Highbiz Trading Sdn. Bhd.. Market feasibility study shows that Bagan Datoh have many agro waste such as vegetables and fruits, fishery and poultry waste, rubber saw dust, oil palm fiber and chicken manure from closed coop. Rubber saw dust and chicken manure were chosen for lab scale formulation study. These two materials were mixed with 1:1 ratio by using rotary drum composter. Composting process was completed within 40 days. Hence, knowledge transfer program will be started by composting of rubber saw dust and chicken manure using windrow system and support with rotary mixing machine specially design by Universiti Putra Malaysia (UPM). At the same time, the discussion with Pertubuhan Peladang Kawasan (PPK) Bagan Datoh is ongoing to work together for commercialization purpose. This project will be roll model to local community and hopefully they will use these agro wastes and have benefits and henceforth increase agriculture and palm oil productivity.